Consensus Statement on Urgent Care Centers and Retail Clinics in Acute Care of Children. Issue 2 (February 2019) - Saidinejad, Mohsen; Paul, Audrey; Gausche-Hill, Marianne; Woolridge, Dale; Heins, Alan; Scott, William Russell; Friesen, Phillip; Rayburn, David; Conners, Gregory; Petrack, Emory; Horeczko, Timothy; Stoner, Michael; et al.
Abstract : Abstract: This article provides recommendations for pediatric readiness, scope of services, competencies, staffing, emergency preparedness, and transfer of care coordination for urgent care centers (UCCs) and retail clinics that provide pediatric care. It also provides general recommendations for the use of telemedicine in these establishments. With continuing increases in wait times and overcrowding in the nation's emergency departments and the mounting challenges in obtaining timely access to primary care providers, a new trend is gaining momentum for the treatment of minor illness and injuries in the form of UCCs and retail clinics. As pediatric visits to these establishments increase, considerations should be made for the type of injury or illnesses that can be safely treated, the required level training and credentials of personnel needed, the proper equipment and resources to specifically care for children, and procedures for safe transfer to a higher level of care, when needed. When used appropriately, UCCs and retail clinics can be valuable and convenient patient care resources.